Microflora of Tropical Legumes’ Seeds for Food Development: Review - Riyanto, Rifqi Ahmad; Utami, Sri (Jurnal Biologi Tropis, 2026)
Tropical legumes are vital for global nutrition but remain underutilized. Their processing relies on indigenous seed microbes, yet a systematic understanding of this microbiome is absent, hindering food safety and innovation. This review aimed to catalog the microbial taxa (bacteria, yeasts, fungi) associated with post-harvest seeds of key tropical legumes like cowpea and pigeon pea. A systematic synthesis of existing literature was performed. Findings reveal a diverse but inconsistently reported microbiome. Core bacterial genera include Bacillus, Lactobacillus, and Enterobacter, with fungi like Aspergillus and Saccharomyces. Data is fragmented, limited by reliance on culture-dependent methods, and lacks functional or quantitative insights. We conclude that tropical legume seeds host a rich, uncharacterized microbial community, prominently featuring lactic acid bacteria (LAB). This represents a significant untapped biotechnological resource. We recommend future research prioritize metagenomic profiling to establish a robust microbial baseline. This should be followed by the functional characterization and development of indigenous LAB consortia as targeted starter cultures to safely optimize traditional fermentations and enhance the value of these crucial crops.